Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of the Positive Modulator of HGF/MET, Fosgonimeton, in Healthy Volunteers and Subjects with Alzheimer’s Disease: Randomized, Placebo-Controlled, Double-Blind, Phase I Clinical Trial - Hua, Xue; Church, Kevin; Walker, William; L’Hostis, Philippe; Viardot, Geoffrey; Danjou, Philippe; Hendrix, Suzanne; Moebius, Hans J. (Journal of Alzheimer's disease, 2022)
Background: Fosgonimeton (ATH-1017) is being developed as a first-in-class regenerative therapy for people with Alzheimer’s disease (AD) and dementia; potentially improving dementia symptoms and altering disease progression by reversing synaptic disconnection and neuronal loss. Objective: This randomized, double-blind, placebo-controlled phase I trial (NCT03298672) evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of fosgonimeton. Methods: Fosgonimeton was administered once daily via subcutaneous injection to 88 subjects. The single ascending dose study enrolled healthy young male subjects (n = 48; age, 33.4±6.3 years; dose, 2, 6, 20, 40, 60, or 90 mg); the multiple ascending dose study enrolled healthy elderly subjects (n = 29; age, 63.8±4.0 years; dose, 20, 40, 60, or 80 mg; 9-day duration); and the fixed-dose study enrolled AD subjects (n = 11; age, 69.2±7.1 years; dose, 40 mg; 9-day duration). Quantitative electroencephalogram (qEEG) and event-related potential (ERP) P300 measured neurophysiological signals following fosgonimeton treatment, supporting brain penetration and target engagement. Results: Fosgonimeton and placebo were shown to be safe and well-tolerated across all doses. Pharmacokinetic results for fosgonimeton were dose-proportional, with no sex effect or accumulation over 9 days. The main effect of fosgonimeton on qEEG was acute and sustained gamma power induction. In AD subjects, there was a significant effect toward ERP P300 latency normalization compared with placebo (p = 0.027; n = 7 at 40 mg fosgonimeton versus n = 4 placebo). Conclusion: These results support the continued development of fosgonimeton as a novel therapeutic for people with AD and dementia. The fast-onset normalization of ERP P300 latency in AD subjects suggests enhancement of synaptic function and potential procognitive effects.